Sex, Power, and Adolescence: Intimate Partner Violence and Sexual Behaviors - Shah, Manisha; Seager, Jennifer; Montalvao, Joao; Goldstein, Markus (The Review of Economics and Statistics, 2025)
Abstract Adolescents in Sub-Saharan Africa face high rates of intimate partner violence (IPV). This paper evaluates the impact of offering adolescent females a goal-setting inter- vention to improve sexual and reproductive health and offering their male partners a soccer-based intervention, which educates and inspires young men to make better sexual and reproductive health choices. Both interventions significantly reduce female reports of IPV. The soccer intervention improves male attitudes around violence and risky sexual behaviors. Females in the goal setting arm take control of their sexual and reproductive health by exiting violent relationships. Both mechanisms drive reductions in IPV.